A detection method of Android system vulnerabilities based on matching - iayuan ZHANGJ (Dianxin kexue)
Android system has occupied the majority share of smart mobile operating systems.However,Android system has worrying security issues.It frequently bursts high-risk vulnerabilities in recent years,which is a big security risk to the majority of Android users.Android system vulnerabilities were studied,and a rapid detection method of Android system vulnerabilities based on matching was proposed.A script-based vulnerability scanning tool was also designed.Through the evaluation of experiments,the tool is running well.